CORBES: radiation belt survey with international small satellite constellation - Wu, Ji; Deng, Li; Praks, Jaan; Anger, Marius; Oleynik, Philipp; Hajdas, Wojciech; Wang, Jin-Dong; Zhang, Shen-Yi; Zhou, Bin; Zeng, Li; Cao, Jinbin; Fischer, David; et al. (Elsevier Ltd, 2025)
The COnstellation of Radiation BElt Survey program (CORBES) is designed to deploy small satellites into a highly elliptic orbit for multi-point exploration of the Earth’s radiation belts. Its scientific objective is to achieve unprecedented high-time-resolution dynamics measurements within the regions of Earth’s outer radiation belts. The CORBES program initiative comprises satellites equipped with three types of payloads: the Magnetometer (MAG), the Search Coil Wave Detector (SCWD), and the High Energy Electron Detector (HEED). The energy interval of HEED is suggested as 0.1-4MeV, logarithmically divided into 12 channels. To ensure extensive coverage of the outer radiation belts, a highly eccentric and inclined orbit is suggested, featuring a perigee of 280 km, an apogee of 7 Earth-Radius (Re), and an inclination of approximately 11 degrees, resulting in an orbital period of approximately 13.5 hours. Within a single orbital period, it takes roughly 10 hours to traverse the outer radiation belts (3 Re to 7Re). All satellites are expected to operate within the same orbit, maintaining a spin-stabilized with sun-pointing spinning axis, and a spinning speed of approximately 8 RPM. Each satellite’s mass should not exceed 30kg. For telecommand, either S-band or X-band will be utilized, while X-band is designated for data downlink. The satellites are scheduled for launch by one or two rockets, with the equipped upper stage placing them into the target orbit, and the attached dispenser releasing them individually according to the required separation sequence. Key aspects of the program include cross-calibration, radiation shielding, assembly integration and testing (AIT). Prior to launch, the cross-calibration is optional for the payloads. The payloads will be tested in the same environment to calibrate the technical specifications. Post-launch, in orbit cross-calibration becomes necessary to maintain data consistency and comparability. Specifically for HEED, this involves selecting electrons with the same energy range during the magnetospheric quiet period(Kp<3), and comparing the observation results of different HEEDs under the same L,B conditions. A similar method applies to MAG and SCWD comparing observations during selected quiet period. Given that the satellites will operate within radiation belts characterized by high-energy protons at low altitudes and electrons at high altitudes, all on-board electronic components must meet fundamental requirements, including shielding geometry structure design, and thickness calculation to mitigate the Total Ionizing Dose Effect (TID) to a level of 200 krad[Si] over a one-year mission cycle. Lastly, system-level AIT before launch could be performed.